2005
DOI: 10.1262/jrd.51.133
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Reproductive Hormone Levels in Pregnant Sows Induced by Repeated ACTH Application and Its Possible Influence on Pre- and Post-natal Hormone Secretion of Piglets

Abstract: Abstract. Prenatal stress has been seen as a reason for reproductive failures in pig offspring mostly originated or mediated by changed maternal functions. Experiments were conducted in pregnant gilts (n=32) to characterize effects of elevated maternal glucocorticoids on the secretion of reproductive hormones (LH, progesterone) during the 1 st (EXP 1), 2 nd (EXP 2) and 3 rd (EXP 3) trimester of pregnancy (TP). Transiently elevated cortisol release was repeatedly achieved by application of 100 IU adenocorticotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…When the data from male and female piglets were combined for analysis, sow treatment had no effect on any litter or piglet characteristic. This is in accordance with previous research results showing that during midgestation neither the authentic stressors of rough handling (Lay et al, 2008) and mixing (Jarvis et al, 2006;Rutherford et al, 2009), nor the artificial stressors ACTH (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Otten et al, 2007) and HCA (Kranendonk et al, 2006) affected gestation length (Haussmann et al, 2000;Jarvis et al, 2006;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008), litter size (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008;Rutherford et al, 2009), or number of stillborn pigs (Haussmann et al, 2000;Jarvis et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…When the data from male and female piglets were combined for analysis, sow treatment had no effect on any litter or piglet characteristic. This is in accordance with previous research results showing that during midgestation neither the authentic stressors of rough handling (Lay et al, 2008) and mixing (Jarvis et al, 2006;Rutherford et al, 2009), nor the artificial stressors ACTH (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Otten et al, 2007) and HCA (Kranendonk et al, 2006) affected gestation length (Haussmann et al, 2000;Jarvis et al, 2006;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008), litter size (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008;Rutherford et al, 2009), or number of stillborn pigs (Haussmann et al, 2000;Jarvis et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008).…”
supporting
confidence: 93%
“…At 0700 h on ED -1 (baseline), 1, 7, and 14 blood was collected from sows in the 3 treatment groups by jugular venipuncture into two 13 × 75 mm, 4.0 mL draw lithium heparin venous blood collection tubes (Becton Dickinson, Franklin Lake, NJ) for plasma cortisol and progesterone analyses. Increased progesterone concentrations have been observed in swine in response to exogenous GC (Schneider et al, 2004;Brussow et al, 2005) and feed restriction (Razdan et al, 2004) which may have androgenic, or conversely, anti-androgenic effects of developing offspring (CohenBendahan et al, 2005). On these days, HCA administration was delayed until after the collection.…”
Section: Gestational Sow Measuresmentioning
confidence: 99%
“…2004a). At later stages of pregnancy, mimicked acute stress (ACTH‐injections at every 10 min during 6 h) did not interfered with pregnancy either; at day 28 of pregnancy the ACTH‐injections caused an increase in basal LH‐levels and a progesterone release and at later stages of pregnancy (day 49 or day 75), these ACTH‐injections furthermore decreased LH‐pulsatility (Brüssow et al. 2005), but these changes did not affect the progress of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the down-regulation of progesterone may be associated with the function of CL. It has been reported that ACTH or cortisol can inhibit the basal secretion of LH and the preovulatory LH surge by reducing GnRH release (38,39). The alteration of LH levels may influence progesterone secretion in CL.…”
Section: Discussionmentioning
confidence: 99%